MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA LAGU ANAK DALAM PEMBELAJARAN IPAS KELAS II DI SDN 2 LIMBOTO - Ahmad, Merlina; Mujahid Damopolii; Karmila Iskandar (Al-mujahidah, 2025)
This research aims to determine the improvement in learning outcomes of class II students at SDN 2 Limboto. In Science Learning. This type of research is classroom action research (PTK). The subjects in this research were class II students at SDN 2 Limboto. The number of students for the 2023/2024 academic year was 24, consisting of 11 boys and 13 girls. This research was conducted in 2 cycles. Each cycle consists of 2 meetings and 4 stages which refers to the Kemmis and Taggart model which consists of 4 stages, namely: planning, action, observation and reflection. The results of this research show that using children's song media can improve student learning outcomes in science and technology learning in class II at SDN 2 Limboto. Data analysis in the research used descriptive percentage formulas for teacher activities, student activities and student learning outcomes. This can be seen from the increase in each cycle, namely cycle I obtained 94% teacher activity, 68% student activity, 63% learning outcomes. And it increased in cycle II to get 100% teacher activity, 96% student activity and 89% learning outcomes. Based on the results of the research conducted, it can be concluded that using children's song media can improve student learning outcomes in science and science learning at SDN 2 Limboto.